2015
DOI: 10.1155/2015/387357
|View full text |Cite
|
Sign up to set email alerts
|

Farnesol, a Sesquiterpene Alcohol in Herbal Plants, Exerts Anti-Inflammatory and Antiallergic Effects on Ovalbumin-Sensitized and -Challenged Asthmatic Mice

Abstract: To investigate the effect of farnesol on allergic asthma, three farnesol doses were extra-added into AIN-76 feed consumed by ovalbumin- (OVA-) sensitized and -challenged mice continuously for 5 weeks, at approximately 5, 25, and 100 mg farnesol/kg, BW/day. The results showed that there were no significant differences in body weight, feed intake, and visceral organ weights between the farnesol supplementation and dietary control groups. Farnesol supplementation decreased interleukin (IL)-6/IL-10 level ratios in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…In other words, the prepared farnesol gel may either simultaneously have high film forming and diffusive properties to more completely cover the outer skin surface (0.5% HPMC; Group B), or averagely possess great stickiness coupled with moderate to high film forming and diffusive capacity (2.0% HPMC; Group E) to achieve satisfactory antiphtoaging and reparative effects on the skin.In ovalbumin‐sensitized and ‐challenged asthmatic mice, farnesol supplementation was found to significantly increase interleukin (IL)‐2 levels and decrease serum IgE and IL‐6/‐10 ratios in bronchoalveolar lavage fluid, suggesting that farnesol may improve allergic asthmatic inflammation in both the respiratory system and the circulation . Our HE and Masson's trichrome staining results also revealed inflammation‐attenuating effects exerted by the prepared plural farnesol gels on the epidermis and dermis in vivo, which is similar to the findings revealed by Ku and Lin . Farnesol has been shown to induce cell cycle arrest in a number of cancer cell types, including lung adenocarcinoma, leukemia, oral squamous carcinoma, and pancreatic adenocarcinoma .…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…In other words, the prepared farnesol gel may either simultaneously have high film forming and diffusive properties to more completely cover the outer skin surface (0.5% HPMC; Group B), or averagely possess great stickiness coupled with moderate to high film forming and diffusive capacity (2.0% HPMC; Group E) to achieve satisfactory antiphtoaging and reparative effects on the skin.In ovalbumin‐sensitized and ‐challenged asthmatic mice, farnesol supplementation was found to significantly increase interleukin (IL)‐2 levels and decrease serum IgE and IL‐6/‐10 ratios in bronchoalveolar lavage fluid, suggesting that farnesol may improve allergic asthmatic inflammation in both the respiratory system and the circulation . Our HE and Masson's trichrome staining results also revealed inflammation‐attenuating effects exerted by the prepared plural farnesol gels on the epidermis and dermis in vivo, which is similar to the findings revealed by Ku and Lin . Farnesol has been shown to induce cell cycle arrest in a number of cancer cell types, including lung adenocarcinoma, leukemia, oral squamous carcinoma, and pancreatic adenocarcinoma .…”
Section: Resultssupporting
confidence: 86%
“…Tea ( Camellia sinensis ) is a commonly used home remedy for sunburn, and Aloe vera or Aloe barbadensis at 100% shows beneficial effects on all types of burn . Farnesol, a component of the plural sunburn gel evaluated in the current study, has previously been found to have topical or systemic anti‐fungal, anti‐bacterial, and inflammation‐modulating effects . These beneficial effects may explain our in vitro results that the gel containing 0.0025% farnesol, 0.5% HA, 0.5% XG, and 2.0% HPMC showed the strongest effects against UVB‐caused reduction in cell viability and accumulation of cell cycle.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…FAR has a broad spectrum of biological activities including antioxidant, anti-inflammatory, anti-allergic, chemo-preventive and anticancer effects. For example, FAR ameliorates serum allergic antibody titres and lipid profiles in ovalbumin-challenged mice [ 2 ], and might have an anti-inflammatory potential to allergic asthmatic mice [ 3 ]. FAR attenuates lipopolysaccharide-induced neurodegeneration in mice by regulating intrinsic apoptotic cascade [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its anti-cancer effects, farnesol exhibits immunomodulatory properties. Recent studies showed that farnesol exhibited anti-inflammatory and anti-allergic effects in a mouse model of allergic asthma and suppressed cellular adaptive immunity [21,22]. A different study reported that farnesol ameliorated cigarette smoke extract-induced inflammation and lung injury [23] and inhibited lipopolysaccharide-induced neuro-degeneration [24].…”
Section: Introductionmentioning
confidence: 99%